Aluminum resistance in common bean (Phaseolus vulgaris) involves induction and maintenance of citrate exudation from root apices - Rangel Becerra, Andrés Felipe; Rao, Idupulapati M.; Braun, HP; Horst, Walter J. (Wiley, 2010)
Two common bean (Phaseolus vulgaris L.) genotypes differing in aluminum (Al) resistance, Quimbaya (Al‐resistant) and VAX‐1 (Al‐sensitive) were grown in hydroponics for up to 25 h with or without Al, and several parameters related to the exudation of organic acids anions from the root apex were investigated. Al treatment enhanced the exudation of citrate from the root tips of both genotypes. However, its dynamic offers the most consistent relationship between Al‐induced inhibition of root elongation and Al accumulation in and exclusion from the root apices. Initially, in both genotypes the short‐term (4 h) Al‐injury period was characterized by the absence of citrate efflux independent of the citrate content of the root apices, and reduction of cytosolic turnover of citrate conferred by a reduced Nicotinamide adenine dinucleotide phosphate–isocitrate dehydrogenase (EC 1.1.1.42) activity. Transient recovery from initial Al stress (4–12 h) was found to be dependent mainly on the capacity to utilize internal citrate pools (Al‐resistant genotype Quimbaya) or enhanced citrate synthesis [increased activities of NAD‐malate dehydrogenase (EC 1.1.1.37) and ATP‐phosphofructokinase (EC 2.7.1.11) in Al‐sensitive VAX‐1]. Sustained recovery from Al stress through citrate exudation in genotype Quimbaya after 24 h Al treatment relied on restoring the internal citrate pool and the constitutive high activity of citrate synthase (CS) (EC 4.1.3.7) fuelled by high phosphoenolpyruvate carboxylase (EC 4.1.1.31) activity. In the Al‐sensitive genotype VAX‐1 the citrate exudation and thus Al exclusion and root elongation could not be maintained coinciding with an exhaustion of the internal citrate pool and decreased CS activity.